Bilayered Clathrin Coats on Endosomal Vacuoles Are Involved in Protein Sorting toward Lysosomes - Sachse, Martin (The American Society for Cell Biology, 2002)
In many cells endosomal vacuoles show clathrin coats of which the function is unknown. Herein, we show that this coat is predominantly present on early endosomes and has a characteristic bilayered appearance in the electron microscope. By immunoelectron miscroscopy we show that the coat contains clathrin heavy as well as light chain, but lacks the adaptor complexes AP1, AP2, and AP3, by which it differs from clathrin coats on endocytic vesicles and recycling endosomes. The coat is insensitive to short incubations with brefeldin A, but disappears in the presence of the phosphatidylinositol 3-kinase inhibitor wortmannin. No association of endosomal coated areas with tracks of tubulin or actin was found. By quantitative immunoelectron microscopy, we found that the lysosomal-targeted receptors for growth hormone (GHR) and epidermal growth factor are concentrated in the coated membrane areas, whereas the recycling transferrin receptor is not. In addition, we found that the proteasomal inhibitor MG 132 induces a redistribution of a truncated GHR (GHR-369) toward recycling vesicles, which coincided with a redistribution of endosomal vacuole-associated GHR-369 to the noncoated areas of the limiting membrane. Together, these data suggest a role for the bilayered clathrin coat on vacuolar endosomes in targeting of proteins to lysosomes.